ANALISIS PENERIMAAN TEKNOLOGI INFORMASI SIMPULSAJI (SISTEM PENGUMPULAN DATA DAN PENYAJIAN INFORMASI) DENGAN MENGGUNAKAN MODEL TAM (TECHNOLOGY ACCEPTANCE MODEL) (Studi Kasus Pada Kantor Pelayanan Pajak Wajib Pajak Besar Tiga) - Deddy Arief Setiwan (Universitas Bunda Mulia, 2017)
This study aims to determine the factors that influence the acceptance of information technology SIMPUSAJI using TAM (Technology Acceptance Model). This TAM include six constructs, namely External Variables, Perceived Ease of Use, Perceived Usefulness, Attitude Toward the Use, Behavioral Intention to Use, and Actual use (Usage). Furthermore External Variables are grouped into three categories, namely organizational factors, social factors, and individual factors. This research model uses extension of TAM undertaken by Venkatesh and Davis (2000) and testing of empirical research conducted by Kim et al. (2009). The research sample uses respondents of structural employee in Large Tax Officer Three. Measurement scale uses indicator variables linkert scale with seven points and the range of value 1 = strongly disagree, and 7 = strongly agree. Techniques of research data analysis use Structural Equation Modeling (SEM) Partial Least Square (PLS) through program of SmartPLS version 2.0. Testing of SEM research consisted of testing the outer model, the inner testing models, and hypothesis. This study proved the extension of TAM model (Venkatesh and Davis, 2000; and Kim et al. 2009). Factors that influence the acceptance of SIMPULSAJI information technology that is used by an structural employee in Large Tax Officer Three is Perceived Usefulness, Attitude Toward Use, Behavioral Intention to Use, and individual factors. Keywords: Acceptance of SIMPUSAJI Information Technology, Perceived Ease of Use, Perceived Usefulness, Attitude Toward the Use, Behavioral Intention to Use, Actual Use (Usage), organizational factors, social factors, and individual factors.